The Relationship between Believing in Resurrection (Ma’ad in Islam) and Self-efficacy in Mothers of Children with Thalassemia - Elham Hesari1 , Fatemeh SHeikhy2 , Nadia Kolbadinezhad3 , Hamid Hojati4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Thalassemia creates many limitations and problems for patients and their families, which decease their selfefficacy, but believing in resurrection can help to alleviate stressful conditions in the life of effected people.This study was designed to investigate the relationship between believing in resurrection and self-efficacyin mothers of children with thalassemia.Method: This descriptive correlational study was performed on 155 parents of adolescents with thalassemiain Golestan province of Iran in 2017, who had been selected by convenience sampling method. Data collectiontools included; believing in resurrection questionnaire and Domka’s parental self-efficacy questionnaire.Data were analyzed by descriptive statistics (mean, standard deviation, tables) and statistical tests (correlationcoefficient of Spearman, U-Mann Whitney and Kruskal Wallis) using SPSS software version 21.Results: The mean score of believing in resurrection was 33.11 ± 6.25 and the mean score of mothers’ selfefficacy was 41.44 ± 6.55. Also, Spearman’s correlation coefficient did not show any significant relationshipwith parental self-efficacy and believing in resurrection (r = 0.1 and p = 0.17).Conclusion: Believing in resurrection shapes the behavior and performance of people in using all theircapacities in difficult situations. Therefore, health managers and practitioners need to pay more attention tothe importance of believing in resurrection and the concept of self-efficacy